Edukasi Tentang Bahaya Resistensi Antibiotik pada Tambak Udang di Kabupaten Pemalang - Linayati, Linayati; Syakirin, Muhammad Bahrus; Supito, Supito; Arifin, Zainul (Pakis Journal Institute, 2026)
Shrimp farming is one of the fisheries industries with good prospects. However, disease outbreaks are one of the main obstacles. Treatment with antibiotics is often the preferred option. The emergence of resistance due to the misuse of antibiotics poses a threat to the environment and human health. This outreach activity aims to provide knowledge about the dangers of antibiotics in aquaculture, especially shrimp ponds. There were 14 participants in the outreach programme, all of whom were BMG pond workers in Pemalang Regency. The outreach method involved direct delivery of information through a PowerPoint presentation displayed via a projector and LCD screen, as well as pre- and post-tests for participants. After the outreach programme, there was a significant increase in knowledge from 10% to 80%. Education through this outreach activity was effective in raising awareness of the dangers of antibiotic resistance in disease control at BMG shrimp farms in Pemalang Regency